OBTAINING ANTIGENIC DIAGNOSTICUM OF THE VIRUS OF INFECTIOUS CANINE HEPATITIS [Text] - Uryumtseva, T.I.; Nikitin, Ye. B.; Yeginbay, Zh. T. (Наука и образование №3, 2019)
International life-stock animals marketing, much of which is intended formeat slaughter, today covers almost all countries of the world. As a component of economic well-being, export-import operations with livestock products can be the cause of the spread of dangerous diseases affecting not only animals, but also humans. The problem of disposal of infected livestock is a matter whose proper solution determines the food security and epizootic well-being of the region. In Pavlodar region there are about three hundred cattle cemeteries, most of which are primitive. Such a situation is typical for the whole Republic, more than 70 % of cattle cemeteries do not meet the requirements and represent as primitive structures. The problem of insufficient provision of the region with livestock disposal sites is solved by the acquisition and use of stationary and mobile incinerators. A separate issue is the anthrax burialdue to the fact that Pavlodar region is characterized by «active risk intensity of anthrax». For the period from 1948 to 2002, 149 foci of anthrax were registered in the region. 131 anthrax burial being a natural reservoir of infection represents a potential threat. It is necessary to maintain these facilitiesproperly, as well as to increase the epizootic safetyliteracy among the population. На настоящий момент в Павлодарской области имеется 283 скотомогильника, из них 28 типовых и 255 примитивных. В области реализуется программа перехода от скотомогильников к инсинераторам, как решение вопроса санитарной и экологической безопасности. На данный момент в Павлодарской области уже используют 19 стационарных и 2 передвижных инсинератора. В Павлодарской области зарегистрировано 149 очагов сибирской язвы: в Актогайском районе- 25, в Баянаульском- 13, в Железинском- 9, в Иртышском- 17, в Качирском- 10, в Лебяжинском- 13, в Майском- 9, в Павлодарском-12, в Успенском- 5, в Щербактинском- 10, в г. Павлодаре- 1, г. Экибастузе- 9, г. Аксу- 16 случаев. На территории Павлодарской области установлено 131 сибиреязвенное захоронение. Все сибиреязвенные захоронения огорожены, имеют стандартные опознавательные знаки. Данные земельные участки внесены в АИСГЗК и получены государственные акты, также заключены договора с РГКП «Казгеодезия». Данные земельные участки закреплены за ГКП «Ветеринарная станция» городов и районов. 131 сибиреязвенное захоронение Павлодарской области представляют эпизоотическую и эпидемическую опасность. Проблема несанкционированного захоронения мелких домашних и сельскохозяйственных животных актуальна по сей день.
Keywords: рк; научный журнал; периодическое издание; отечественное издание; скотомогильник; инсинератор; утилизация трупов; ветеринария